Neurovisualisation of the hippocampus: role in diadnostic of the early alzheimer disease - N. G. Neznanov; N. I. Ananyeva; N. N. Zalutskaya; E. V. Andreev; L. R. Akhmerova; R. V. Ezhova; T. A. Salomatina; I. K. Stulov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In our study we have analyzed MRI of mediobasal parts of temporal lobes in healthy volunteers and patients with Alzheimer disease in early stage based on medical literature and our experience. We have determined method of defnition and volume evaluation of diﬀerent hippocampal subfelds.